Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Minat Belajar Matematika Kelas V SDN Ciporos 01 - Aisyah, Delia Noer; Azizah, Amalia Nurul; Kurniawan, Alfi Muklis (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of the Jigsaw cooperative learning model on the interest in learning mathematics among fifth-grade students at Ciporos 01 Public Elementary School. This study used a quantitative method with a one-group pretest-posttest design. The research sample consisted of all 16 fifth-grade students. Data were collected through interviews, questionnaires, observations, and documentation. Data analysis was performed using SPSS 16.0 through prerequisite tests (normality and homogeneity tests) and hypothesis testing using a paired sample t-test to compare the average pretest and posttest results. The results showed that the students' pretest scores ranged from a high of 89 to a low of 61, with an average of 73.19. Meanwhile, the posttest scores showed a highest score of 94, a lowest score of 82, and an average of 89.56. A comparison of these two data sets shows an increase of 16.375%. Based on the results of the analysis, it can be concluded that the Jigsaw cooperative learning model has a positive effect on increasing students' interest in learning mathematics.